Integrated design by optimization of electrical energy systems - Roboam, Xavier. (ISTE Ltd., 2012)
"This book presents the vision of French academics about systemic design methodologies applied to electrical energy systems. It is especially dedicated to discussion of analysis and system management, as well as modeling and sizing tools"--